Analysis of the Contribution of the Processing Industry Sector in Efforts to Reduce Poverty in North Sumatra Province - Indrayani, Ilham Dandi; Sembiring, Rahmad (Journal of Community Research and Service, 2024)
This study aims to analyze the contribution of the processing industry to efforts to reduce poverty in North Sumatra Province, analyze the influence of the number of industries, investment, exports on industrial GDP and the number of population, unemployment on the poverty rate. This study uses secondary data in the form of time series data, 2009-2023, namely data on the number of industries, PMDN investment in the processing industry, Industrial Exports, the number of population, unemployment, Industrial GDP, and poverty in North Sumatra province. The analysis method used is simultaneous regression. The results of the study show that the influence of the number of industries has an impact on the increase in industrial GDP, and the number of population also has an impact on the increase in poverty, then the industrial GDP does not have a significant impact on poverty in North Sumatra Province.